The Role of Journalists in Socializing Money Waqf - M. Yoserizal Saragih (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This study aims to determine the role of journalists in socializing money waqf. This study use qualitative research. The role of journalism is a certain set of behaviors caused by a journalist (journalist) who collects, manages, writes, edits data, so as to produce information or news, whose information is about daily events, periodically using existing mass media facilities. In role theory explains that the role is a point of view insociologyandsocial psychology which assumes that most daily activities are carried out by socially defined categories. Journalism plays an important role in disseminating messages or news to the public with the aim of disseminating something that is considered important to the community. The role of journalism in disseminating cash waqf to the public is as follows:agents of reform, social control tools, public educators, information providers, broadening horizons of thought, focusing attention, fostering aspirations, creating a constructive atmosphere, acting as a bridge, being able to recognize social norms, being able to cultivate tastes andable to change a weak attitude into a stronger attitude.